GANGGUAN PERILAKU STUDI KASUS PADA ANAK TANPA AYAH DI JEMAAT GPM DIAN - Lolita L Ririhena; Elvi Eleuwarin (TANGKOLEH PUTAI, 2018)
The study of children without father in Dian GPM congregation departed from the researcher's concern about the adolescents gang observed in the research village. Behavioral disorder or behavior disorder is a recurring pattern of behavior in which the basic rights of others or norms in society are violated, manifested in the presence of three (or more) of the following criteria in the past 12 months, and at least one criterion must exist within the last 6 months , according to DSM (Diagnostic of Statistical Manual of Mental Disorder). The purpose of this study is to get a psychological picture of how the behavioral disorders of children without the father, emerged. This research is a qualitative research where observation and interview are used as data collection technique, using analytical descriptive analysis technique. The results of this study indicate that children without fathers have behavioral disorders and are involved in gangs as a way of maintaining and protecting low self-esteem due to psychological injuries due to the absence of a father figure in their lives.